An Epidemic of Pride: Pellagra and the Culture of the American South - Crabb, Mary Katherine (Anthropologica, 2022)
A large epidemic of pellagra, a nutritional deficiency disease of the B vitamin, niacin, broke out in the American South in the early 1900s. In epidemiological and nutritional literature the discovery of niacin and the conquest of pellagra are often portrayed as straight forward medical victories. However, when the true etiology of the disease was first discovered by Dr. Joseph Goldberger (a New Yorker), his results were angrily denounced by southern physicians, legislators and the general public. Nearly 20 years elapsed before his conclusions were finally accepted and a co-ordinated public health effort was begun. The reasons for this irrational Southern response are specifically related to the cultural identity and values of the South at this time. Parallel exploration of the history of the pellagra epidemic and the unique culture of the South provides powerful insights into how culture can negotiate the acceptable parameters of scientific research.